The incidence and clinical characteristics of fragile X syndrome in China - Mei, Lianni; Hu, Chunchun; Li, Dongyun; Wang, Ya; Li, Huiping; Zhang, Kaifeng; Zhou, Bingrui; Zhu, Ruoping; Hagerman, Randi J.; Xu, Xiu; Xu, Qiong (Frontiers in Pediatrics, 2023)
The purpose of this study is to investigate the incidence of FXS in Chinese children and analyze the comprehensive clinical characteristics of these FXS children. Children diagnosed with idiopathic NDD were recruited between 2016 and 2021 from the department of Child Health Care, Children’s Hospital of Fudan University. We combined tetraplet-primed PCR-capillary electrophoresis and WES/panel or array-CGH to identify the size of the CGG repeats and the mutations or CNV in the genome and in FMR1. The clinical features of FXS children were analyzed according to pediatricians’ recording, parental questionnaires, the results of examinations and follow-up. The incidence of FXS in Chinese children with idiopathic NDD was 2.4% (42/1753) and in those with FXS 2.38% had a deletion (1/42). We present here the clinical characteristics of 36 children with FXS. Overweight had been observed in two boys. The average IQ/DQ of all FXS patients were 48. The average ages of meaningful words and walking alone were 2 y 10 mo and 1 y 7 mo respectively. The most frequent repetitive behavior was stimulated by hyperarousal to sensory stimulation. In social aspect, social withdrawal, social anxiety and shyness accounted for 75%, 58% and 56% of the total number of children, respectively. About 60% of FXS children in this cohort were emotionally labile and prone to temper tantrums. Self-injury and aggression towards others could also be observed, at 19% and 28% respectively. The most frequent behavior problem was ADHD seen in 64% and the most common facial features were narrow and elongated face and large or prominent ears, present in 92% of patients. In conclusion, we provided data on the epidemiology and clinical characteristics of FXS in China.